Application of the Prototype Model in Cooperative Profile Web Application Design - Enda, Depandi; Supria, Supria; Wahyat, Wahyat (International Conference on Sciences Development and Technology, 2022)
The development of information technology has triggered everyone in the business world, including cooperatives, to change the service system that was initially conventional to switch to digital. This is because the traditional business approach has several shortcomings in disseminating information on cooperative business profiles to external parties, such as limited access to information, slow dissemination of information, and being time-consuming and costly. For this reason, developing a business profile web application is needed to provide efficient access to information without limitations of space and time. However, there is a problem with how to design an application that fits the needs and meets user expectations. The prototype model can be used as a benchmark for an application, whether it is feasible to implement or not, following the results of the evaluation of user satisfaction. So, in this study, it is proposed to apply a prototype model to design applications that suit the needs and expectations of users. The application's design has been assessed using a questionnaire distributed to 30 respondents. The average result of the feasibility of the prototype design made is 93.05%, with a very feasible category.